The Effectiveness of the External Support on the Strength and Muscle Activity of Hip Abductor in Subject Without Core Stability - In-Cheol Jeon (Korean Research Society of Physical Therapy, 2022)
Background: Gluteus medius muscle is important for the stability of hip joint. The sufficient core stability can be contributed to the performance of gluteus medius muscle in standing position. In addition, the external support may affect core stability in standing position. Objects: The purpose of this study was to investigated the effectiveness of the external support on the strength and muscle activity of hip abductor muscle during hip abduction in standing position in subjects without core stability. Methods: Fifteen subjects participated in this study. The subjects were evaluated by using the double-leg lowering with bent knees to measure the core stability. The strength and muscle activity of hip abductors was measured in standing position with the condition with and without external support using the tensiometer sensor and the surface electromyography. The paired t-test was used to investigate the difference between hip abductor strength and activity according to external support. The level of statistical significance was set at α = 0.05. Results: The hip abductor strength and muscle activity of gluteus medius muscle with external support were significantly greater than those without external support during hip abduction in standing position (p < 0.05). Conclusion: During hip abduction in standing position, the external support may be contributed to the improvement of the hip abductor strength and muscle activity of gluteus medius especially in the subjects without core stability.